Taking a stand : contemporary US stand-up comedians as public intellectuals - Champion, Jared N.; Kunze, Peter C. (Peter Christopher) (University Press of Mississippi, 2021)
"Stand-up comedians have a long history of walking a careful line between serious and playful engagement with social issues: Lenny Bruce questioned the symbolic valence of racial slurs, Dick Gregory took time away from the stage to speak alongside Martin Luther King Jr., and-more recently-Tig Notaro challenged popular notions of damaged or abject bodies. Taking a Stand: Contemporary US Stand-Up Comedians as Public Intellectuals draws together essays that contribute to the analysis of the stand-up-comedian-as-public intellectual since the 1980s. The chapters explore stand-up comedians as contributors to and shapers of public discourse via their live performances, podcasts, social media presence, and political activism. Each chapter highlights a stand-up comedian and their ongoing discussion of a cultural issue or expression of a political ideology/standpoint: Lisa Lampanelli's use of problematic postracial humor, Aziz Ansari's merging of sociology and technology, or Maria Bamford's emphasis on mental health, to name just a few. Taking a Stand offers a starting point for understanding the work stand-up comedians do as well as its reach beyond the stage"--